Empowering Women through Microfinance: Evidence from Pakistan (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of the study is to investigate the relationship between microfinance and women's empowerment. To achieve the objective, data was collected from 350 women from rural areas of Shaheed Benazir Abad district using a simple random sampling technique. A structured questionnaire was adopted from previous studies to collect the data. As per Kolmogorov-Smironov and Shapiro-Wilk tests, the data was not normal. Therefore, we used Mann-Whitney and Kruskal-Wallis tests to test the hypothesis. Income saving, living standard, household wellbeing, and social status were used as the indicators of women's empowerment. Tests were run based on the presence of microfinance usage, loan amount, and loan duration. As per the results, there is a significant positive relationship between microfinancing and all of the indicators of women empowerment during loan amount and loan duration. Thus, it is concluded that there is a strong association between microfinance and women's empowerment.